Unlocking Potential Benefits on Applications of Probiotics in Inland Aquaculture Industry: A Review - Kelvin E. Vulla; Francis P. Mmanda; Baraka P. Nyangoko; Edna E. Makule (Aquaculture, Fish and Fisheries)
ABSTRACT Inland aquaculture operations are practised all over the world, contributing about 62.6% of all farmed aquatic animals. This venture is increasing worldwide and outpacing the global market demand for fish and fishery products driven by competition with other animals, over‐population and over‐exploitation of wild capture fisheries. These operations expand globally, associated with the degradation of the culture environment due to poor aquaculture management practices and algal blooms due to nutrient influxes as well as high demand of quality fish feeds of affordable price. To overcome these challenges, sustainable, healthy and environmentally friendly alternatives including probiotics application must be adopted to achieve better production, profitability and productivity as well as a resilient culture environment. In this review, information on potential applications of probiotics in aquaculture (inland aquaculture) focused on sources, safety, approved probiotics for aquaculture, characteristics of probiotics, mode of applications and its potential use on pathogenic microbes control, fish haematological parameters, growth performance and stress responses, water quality parameter, anti‐nutritional factors and feed digestibility, limitation of using probiotics in aquaculture and lastly future perspectives on the probiotics application in aquaculture industry were reviewed and compiled for future sustainable aquaculture production and productivity and environmentally friendly. The review has also highlighted all probiotics application and their approved authority for use in farmed freshwater fish (Nile tilapia Oreochromis niloticus, Catfish Clarias gariepinus, rainbow trout Oncorhynchus mykiss and common carp Cyprinus carpio) and their cultured environment worldwide. Therefore, the review has comprised all information on the potential benefits application of probiotics in an inland aquaculture for public documentation and also identifies gaps in the aquaculture industry that require further research and assessment.